Small vs luxury cars: what is the coherent strategy for MNCs to survive in india's automobile market?. Issue 6 (11th June 2018) - Kaushal, Leena Ajit
Abstract : Purpose: The purpose of teh paper is to Explore why MNCs are not able to compete in Indian automobile industry and have very minimal market share. Design/methodology/approach: Its a view point based on market intelligence. Findings: In the circumstances where India consumers have abundant bargaining power due to the access to variety of products available in the same range, by different manufacturers, the MNCs can compete in the Indian market only by adopting local strategy and understanding local mindset of the customers. Researchlimitations/implications: The study suggest that the MNCs can compete in the Indian market only by adopting local strategy and understanding local mindset of the customers. Practical/implications: Its quite useful for MNCs planning to explore Indian automobile market. Practical/implications: India has allowed 100 per cent FDI in Automobile sector. If MNCs strategically plan to cater to teh Indian consumers, that can help us upgrade technology and provide employment o our countrymen. Originality/Value: Its a viewpoint.